The summer of the swans - Byars, Betsy Cromer; Coconis, Constantinos (New York : Viking Press, 1970)
A teen-age girl gains new insight into herself and her family when her mentally retarded brother gets lost.
830
Newbery Medal, 1971
Keywords: People with mental disabilities -- Fiction